Smart Lighting Operation for The Growth of Bird's Eye Chili Plants Using Arduino Uno - Supandri, Muhammad Hamdu; Wirateruna, Efendi S; Basuki, Bambang Minto (Universitas Islam Malang, 2024)
Unfavorable weather conditions, climate change, and pests can disturb chili cultivation. The